STRATEGY ANALYSIS OF THE MARKETING MIX IN THE DIGITAL ERA AND THE INFLUENCE ON PRODUCT SALES AT PT. WORLD INNOVATIVE TELECOMMUNICATION MEDAN BRANCH - Kamelia Tania; Calvin Fernando; Cerly Wyke Ferontica; Andre Fitriano (Jurnal Mantik, 2022)
Product, price and promotion are elements that can affect sales. This study aims to determine and analyze the effect of product, price and promotion on the sales of PT. World Innovative Telecommunication Medan branch. This type of research is explanatory research. The research population that will be used in the study is all customers who make purchases at the company with a total population of 1,941 customers. Due to the total population which only amounts to 1,941 customers, the sampling technique that will be used is the Slovin formula and obtained as many as 95 people. In this research, the distribution of questionnaires will be measured using a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that either partially or simultaneously, product, price and promotion had a positive and significant effect on sales of PT. World Innovative Telecommunication Medan branch. Based on the results of this study, the implications for management are to improve products, prices and promotions.